Effect of concurrent sexual partnerships on rate of new HIV infections in a high-prevalence, rural South African population: a cohort study - Tanser, Frank; Bärnighausen, Till; Newell, Marie-Louise (The lancet, 2011)
Summary: Concurrent sexual partnerships are widely believed to be one of the main drivers of the HIV epidemic in sub-Saharan Africa. This view is supported by theoretical models predicting that increases in prevalence of concurrent partnerships could substantially increase the rate of spread of the disease. However, the effect of concurrent partnerships on HIV incidence has not been appropriately tested in a sub-Saharan African setting. For this population-based cohort study, we used data from the Africa Centre demographic surveillance site in KwaZulu-Natal, South Africa, to try to find support for the concurrency hypothesis. We used a moving-window approach to construct estimates of the geographical variation in reported concurrent and lifetime partners in sexually active men aged 15-55 years (n=2153) across the study area. We then followed up 7284 HIV-negative women (≥15 years of age) in the population and quantified the effect of the sexual behaviour profiles of men in the surrounding local community on a woman's hazard of HIV acquisition. During 5 years' follow-up, 693 new female HIV infections occurred (incidence 3·60 cases per 100 person-years). We identified substantial intercommunity heterogeneity in the estimated point-prevalence of partnership concurrency (range 4·0-76·3%; mean 31·5%) and mean number of lifetime sexual partners (3·4-12·9; mean 6·3) in sexually active men in this population. After adjustment for individual-level sexual behaviour and demographic, socioeconomic, and environmental factors associated with HIV acquisition, mean lifetime number of partners of men in the immediate local community was predictive of hazard of HIV acquisition in women (adjusted hazard ratio [HR] 1·08, 95% CI 1·03-1·14, p=0·004), whereas a high prevalence of partnership concurrency in the same local community was not associated with any increase in risk of HIV acquisition (adjusted HR 1·02, 95% CI 0·95-1·09, p=0·556). We find no evidence to suggest that concurrent partnerships are an important driver of HIV incidence in this typical high-prevalence rural African population. Our findings suggest that in similar hyperendemic sub-Saharan African settings, there is a need for straightforward, unambiguous messages aimed at the reduction of multiple partnerships, irrespective of whether those partnerships overlap in time. US National Institute of Child Health and Human Development; Wellcome Trust.